2012
DOI: 10.1038/eye.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Combining corneal hysteresis with central corneal thickness and intraocular pressure for glaucoma risk assessment

Abstract: Purpose To determine whether adjusting corneal hysteresis (CH) values for central corneal thickness (CCT) and intraocular pressure (IOP) improves its capability to differentiate primary open-angle glaucoma (POAG) from ocular hypertension (OH). Methods This prospective, observational, cross-sectional study included 169 eyes of 169 subjects with a diagnosis of POAG (n ¼ 81) or OH (n ¼ 88). We utilized the Ocular Response Analyzer (ORA), Pascal Dynamic Contour Tonometer (DCT), Goldmann applanation tonometer (GAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
1
29
0
3
Order By: Relevance
“…Prior studies using the ORA have demonstrated that glaucomatous eyes exhibit distinctly different biomechanical profiles as compared with nonglaucomatous eyes. [10][11][12][13][14][15][16][17][18][19][20][21][22] However, subsequent studies have shown that CH is moderately correlated with both IOPdependent and CCT-dependent variable with reported Pearson correlation coefficients ranging from 0.33 to 0.52. [34][35][36] Our work is the first, to the best of our knowledge, to describe a novel corneal biomechanical parameter-highest concavity time-which correlates with glaucomatous disease and is not associated with previously validated risk factors such as IOP, CCT, and age.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Prior studies using the ORA have demonstrated that glaucomatous eyes exhibit distinctly different biomechanical profiles as compared with nonglaucomatous eyes. [10][11][12][13][14][15][16][17][18][19][20][21][22] However, subsequent studies have shown that CH is moderately correlated with both IOPdependent and CCT-dependent variable with reported Pearson correlation coefficients ranging from 0.33 to 0.52. [34][35][36] Our work is the first, to the best of our knowledge, to describe a novel corneal biomechanical parameter-highest concavity time-which correlates with glaucomatous disease and is not associated with previously validated risk factors such as IOP, CCT, and age.…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies have demonstrated statistically significant differences between CH and corneal resistance factor in patients with various categories of glaucomatous disease, including primary open-angle glaucoma, [10][11][12][13][14][15][16] primary angle closure glaucoma, 17,18 and normal tension glaucoma 12,[19][20][21][22] from normal eyes. Although there is conflicting evidence as to whether or not corneal biomechanical parameters are truly pressure-independent risk factors for glaucoma, 16,23 newer studies suggest that corneal biomechanical parameters may be able to predict the development and progression of this disease for individuals.…”
mentioning
confidence: 99%
“…A wide variety of other applications of ocular sonography, both as a clinical tool and a research tool, have been reported in the literature as well, including evaluation of patients with glaucoma, identification of ocular foreign bodies, diagnosis of a variety of acute and chronic problems, and even many veterinary applications. [27][28][29][30] …”
Section: Clinical Utilization Of Ophthalmic Ultrasoundmentioning
confidence: 99%
“…In this study, we defined macrodiscs as larger than 2.80 mm 2 . Normal disc size was defined as disc area between 1.4 and 2.80 mm 2 (11).…”
Section: Methodsmentioning
confidence: 99%
“…The Ocular Response Analyzer (ORA) (Reichert Inc., Depew, NY, USA) evaluates biomechanical properties of the cornea in situ. Corneal hysteresis (CH) measurement obtained using ORA demonstrates cornea's ability to dampen and buffer fluctuations in IOP (2).…”
Section: Introductionmentioning
confidence: 99%